Applicative Characteristics of a New Zirconia Bracket with Multiple Slots - Koutaro Maki; Katsuyoshi Futaki; Satoru Tanabe; Mariko Takahashi; Yuta Ichikawa; Tetsutaro Yamaguchi (International Journal of Dentistry)
We have developed a new orthodontic bracket with three slots with lubricative properties on the working surfaces and proposed a new orthodontic treatment system employing 0.012−0.014-inch Ni-Ti arch wires. We recruited 54 patients, of which 27 received treatment with the new zirconia bracket with multiple slots system (M group), and the others received treatment with standard edge-wise appliances (control group [C group]). We compared the (1) tooth movement rate at the early stage of leveling; (2) changes in the dental arch morphology before and after leveling; and (3) pain caused by orthodontic treatment. Student’s t-test was used in all assessments. The tooth movement rate in the maxillomandibular dentition was higher in the M group. The basal arch width, anterior length, and the intercanine width in the maxillary dentition were not significantly different in the two groups; however, the intercanine width in the mandibular dentition was higher in the C group. In assessments of treatment-related pain, the visual analogue pain score was 56.0 mm and 22.6 mm in the C and M groups, respectively. A new zirconia bracket with multiple slots system provided better outcomes with respect to tooth movement rate, treatment period, and postoperative pain, thus indicating its effectiveness over conventional orthodontic systems.